SPATIOTEMPORAL DISTRIBUTION OF THE OLIVE PSYLLID EUPHYLLURA OLIVINA COSTA, 1839 (HEMIPTERA: PSYLLIDAE) ON THE CHEMLAL VARIETY IN THE MOUNTAINS OF KABYLIE – ALGERIA - Hamdani Mourad; Hoceini Faiza; Sellami Mahdi (Natural Resources and Sustainable Development, 2023)
The study conducted on the population dynamics and the spatiotemporal distribution of the olive psyllid Euphyllura olivina on two olive groves, of the Chemlal variety, in the Kabylie Mountains, one is located in the wilaya of Bouira (Station Mchedallah) and the other in the wilaya of Tizi Ouzou (Station ITMAS Boukhalfa), revealed that the first numbers of the different biological stages appeared in February 2022. The first numbers of eggs of E. olivina, are recorded in mid-February 2022 for the station of Mchedallah, with a low number, while, for the station of Boukhalfa, the first numbers are recorded in mid-April 2022 and then progress to reach a peak of 56 eggs on May 22, 2022. The numbers of larvae, are high for the different larval stages of the psyllid, during the spring period of the year 2022 in both study stations. The high mortality rate is about 29.07% on the North direction, then the other directions the rates are close to 24% in the station of Mchedallah and in the station of Boukhalfa the South direction records the highest rate with 37.35% followed by the North direction with 32.53 %.